Impacts of land redistribution on land management and productivity in the Ethiopian highlands - Benin, Samuel; Pender, J.L. (International Livestock Research Institute, 2002)
The increasing problem of landlessness in Ethiopia has put pressure on regional governments to redistribute land. In 1997 and 1998, a major land redistribution exercise was undertaken in the Amhara region, reducing landlessness where implemented. While the impacts of such redistributions have been hotly debated, little empirical evidence exists concerning the actual impacts of redistribution. We find that land redistribution in Amhara region has had a positive impact on land productivity, by increasing access to land of farmers who are more interested or able to use purchased inputs such as fertiliser and herbicides. Our results, however, do not show much effect of the recent land redistribution or expectations of future redistribution on land improvement and management. Thus, to the extent that investment in land improvement are necessary for conservation purposes, it appears that policy change to stop land redistributions is unlikely to have a substantial impact on reducing land degradation. Credit and extension programs and improving land rental markets, however, present better strategies for improving land management in this region of Ethiopia.